Functional Neuroanatomy of the Rat Nucleus Incertus–Medial Septum Tract: Implications for the Cell-Specific Control of the Septohippocampal Pathway - Szlaga, Agata; Sambak, Patryk; Trenk, Aleksandra; Gugula, Anna; Singleton, Caitlin E.; Drwiega, Gniewosz; Blasiak, Tomasz; Ma, Sherie; Gundlach, Andrew L.; Blasiak, Anna (Frontiers in Cellular Neuroscience, 2022)
The medial septum (MS) is critically involved in theta rhythmogenesis and control of the hippocampal network, with which it is reciprocally connected. MS activity is influenced by brainstem structures, including the stress-sensitive, nucleus incertus (NI), the main source of the neuropeptide relaxin-3 (RLN3). In the current study, we conducted a comprehensive neurochemical and electrophysiological characterization of NI neurons innervating the MS in the rat, by employing classical and viral-based neural tract-tracing and electrophysiological approaches, and multiplex fluorescent in situ hybridization. We confirmed earlier reports that the MS is innervated by RLN3 NI neurons and documented putative glutamatergic (vGlut2 mRNA-expressing) neurons as a relevant NI neuronal population within the NI–MS tract. Moreover, we observed that NI neurons innervating MS can display a dual phenotype for GABAergic and glutamatergic neurotransmission, and that 40% of MS-projecting NI neurons express the corticotropin-releasing hormone-1 receptor. We demonstrated that an identified cholecystokinin (CCK)-positive NI neuronal population is part of the NI–MS tract, and that RLN3 and CCK NI neurons belong to a neuronal pool expressing the calcium-binding proteins, calbindin and calretinin. Finally, our electrophysiological studies revealed that MS is innervated by IA current-expressing, type I NI neurons, and that type I and II NI neurons differ markedly in their neurophysiological properties. Together these findings indicate that the MS is controlled by a discrete NI neuronal network with specific electrophysiological and neurochemical features; and these data are of particular importance for understanding neuronal mechanisms underlying the control of the septohippocampal system and related behaviours.